The effect of rest interval length on metabolic responses to the bench press exercise - Ratamess, N. A.; Falvo, M. J.; Mangine, G. T.; Hoffman, J. R.; Faigenbaum, A. D. (European Journal of Applied Physiology, 2007)
The purpose of this study was to examine the effects of different rest interval (RI) lengths on metabolic responses to the bench press. Eight resistance-trained men performed 10 randomized protocols [five sets of bench press with 75 or 85% of 1RM for ten (10REP) and five repetitions (5REP), respectively, using different RI (30 s, 1, 2, 3, 5 min)]. Oxygen consumption (VO2) was measured during exercise and for 30 min post exercise. For 30-s and 1-min RI: reductions (15-55%) in resistance and volume were observed (set 5 < 4 < 3 < 2 < 1). For 2-min RI: performance was maintained during the first two sets but was reduced by 8-29% during sets 3-5. For 3-min RI: a reduction was observed in volume where sets 4 and 5 were lower than sets 1-3 (~21%). For 5-min RI: only a reduction in set 5 was observed. Mean VO2 and ventilation (V E) were progressively higher as RI length was shortened. VO2 area under the curve indicated 10REP > 5REP for all RI except 1-min. Respiratory exchange ratio (RER) was elevated similarly for each protocol. Post exercise, VO2, V E, and RER were elevated through 30 min. No differences between RI were observed following 10REP; however, VO2 after 30-s was higher than 2-, 3-, and 5-min and 1-min was higher than 5-min during 5REP. Fatigue rate was correlated (r = 0.30-0.49) to all metabolic variables. A continuum of performance reductions and metabolic responses were observed. The largest reductions in performance occurred with very short RI (<1 min), and performance was maintained during the first 3-4 sets when 3- and 5-min RI were used.